Book Reviews. Issue 3 (1st September 2015) - Wheeler, Duncan; Venegas, Cristina; López, Marina Díaz; Tierney, Dolores; Rêgo, Cacilda M.; Healy, Lynn
El documental Cinematográfico y Televisivo Contemporáneo: Memoria, Sujeto y Formación de la Identidad Democrática Española, Isabel M. Estrada (2013) Woodbridge: Tamesis, 196 pp., ISBN: 9781855662513, h/bk, £60.00La Televisión Durante La Transición Española, Manuel Palacio (2012) Madrid: Cátedra, 453 pp., ISBN: 9788437630687, h/bk, €23.40El Cine Y La Transición Política En España (1975–1982), Manuel Palacio (ed.) (2011) Madrid: Biblioteca Nueva, 271 pp., ISBN: 9788499402987, p/bk, €16.00Indianizing Film: Decolonizing, The Andes, and The Question of Technology, Freya Schiwy (2009) New Jersey: Rutgers University Press, 282 pp., ISBN: 9870813545400, p/bk, US 24.95; ISBN: 9780813547138, web pdf, US 24.95All about Almodóvar. A Passion for Cinema, Brad Epps and Despina Kakoudaki (eds) (2009) Minneapolis and London: University of Minnesota Press, 496 pp., ISBN: 9780816649617, p/bk, US18Screening Cuba: Film Criticism as Political Performance during the Cold War, Hector Amaya (2010) Urbana and Chicago: University of Illinois Press, 222 pp., ISBN: 9780252035593, cloth, US 80.00; ISBN: 9780252077487, p/bk, US 30.00; ISBN: 9780252090028, e-bookBrazilian Women's Film-making: From Dictatorship to Democracy, Leslie L. Marsh (2012) Urbana, Chicago and Springfield: Illinois University Press, 248 pp., ISBN: 9780252037252, cloth, US 85.00; ISBN: 9780252078736, p/bk, US 28.00; ISBN: 9780252094378, e-bookLatsploitation, Exploitation Cinemas and Latin America, Victoria Ruétalo and Dolores Tierney (eds) (2009) New York: Routledge, 328 pp., ISBN: 0415993865, p/bk, US 54.95